Laboratory And Field Studies On The Bionomics Of Culex Quinquefasciatus Say (Diptera: Culicidae) In Pulau Pinang, Malaysia - Hamzah, Siti Nasuha (2010)
The biting cycle and seasonal abundance of Culex quinquefasciatus mosquito were studied for 14 months from February 2008 to Mac 2009 in Penang using the bare-leg-catch technique. Twelve hours collections (1900-0700 hours) were conducted to determine the biting cycle of Cx. quinquefasciatus whereas five-hour collections (2100-0100 hours) were conducted to determine its seasonal abundance.